Reporting Domestic Violence in Florida - Kathleen Beall; Heidi Radunovich (EDIS)
Being in a violent relationship can be both a terrifying and hopeless experience. Likewise, the legal process can be both an extensive and complicated process. In this 2-page fact sheet, we address what to expect when reporting the violence to law enforcement. Written by Kathleen Beall and Heidi Radunovich, and published by the UF Department of Family, Youth and Community Sciences, December 2014.